Are CD68 and Factor VIII-RA Expression Different in Central and Peripheral Giant Cell Granuloma of Jaw: An Immunohistochemical Comparative Study - Soudabeh SARGOLZAEİ; Nasim TAGHAVİ; Farzaneh POURSAFAR (Federation of Turkish Pathology Societies, 2018)
Objective: Central giant cell granuloma and peripheral giant cell granuloma of the jaw and oral cavity are identical in histopathologic features, although they are different in pathogenesis and clinical behavior. The aim of present study was to compare CD 68 and factor VIII related antigen (VIII-RA ) immunoreactivity in central giant cell granuloma and peripheral giant cell granuloma to determine the biologic nature and clinical behavior of these lesions which may lead to a better or new treatment modality. Material and Method: CD68 and factor VIII-RA expression were examined immunohistochemically in 22 cases of central giant cell granuloma (10 aggressive and 12 non- aggressive ) and 19 cases of peripheral giant cell granuloma. The Kruskal-Wallis test followed by the Dunn test was used for data analysis. Results: CD68 expression was observed in approximately 100% of multinucleated giant cells and 50% of mononuclear cells. Overexpression of factor VIII-RA in the endothelial cells of capillary like vessels in the periphery of the lesions was prominent. A statistical significant difference for CD68 intensity score in mononuclear cells among three groups (P=0.016) was observed. Indeed, factor VIII-RA intensity score in the endothelial cells of central giant cell granuloma and peripheral giant cell granuloma showed significant difference (P=0.004). Conclusion: These findings support the histiocyte/macrophage nature of multinucleated giant cells and mononuclear cells. Overexpression and high intensity score of CD68 in mononuclear cells and the high intensity score of factor VIII-RA in endothelial cells represent less aggressive behavior in central giant cell granuloma.